One hundred great books on typography the ultimate typographic library - Toromanoff, Agata (Luster, 2016)
"This book presents the reader with one hundred valuable and influential books on the subject. Thematic sections allow the reader to navigate easily, and thorough reviews explain the importance of each book. This versatile collection is the ideal library for anyone who wants to know how type works and, more importantly, how to use it. The book also contains three interviews with typography experts and authors of influential books on the subject."==